Improving BER and data throughput using adaptive modulation level MC-CDMA technique in underwater wireless communication - T, Jaya.; Vijayalakshmi, P; Rajendran, V (International Journal of Engineering and Technology, 2018)
Underwater communication has a wide range of applications like environmental monitoring to predict the natural disasters, underwater ex-ploration and military applications. The need for effective underwater communication is the high demand in the present scenario. The im-plementation of precise modulation technique is also important because the underwater channel environment is time variant due to various noises present in the underwater like natural and vehicle noise (mechanical noises). The bandwidth is also highly limited in underwater communication. The existing method is adaptive modulation based OFDM system. This method has low spectral efficiency, however, each symbol is modulated with different carriers. The proposed method is Adaptive Modulation Level MC-CDMA (Multi carrier Code Division Multiple Access). The CDMA techniques share the same carrier frequency to multiple number of users. It adapts the modulation scheme according to the present channel conditions in the underwater. The performance of the proposed system improves the Data Throughput and Bit Error Rate.Â